2004
DOI: 10.1091/mbc.e03-09-0640
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk of Integrin α3β1 and Tissue Factor in Cell Migration

Abstract: In cancer and angiogenesis, coagulation-independent roles of tissue factor (TF) in cell migration are incompletely understood. Immobilized anti-TF extracellular domain antibodies induce cell spreading, but this phenomenon is epitope specific and is not induced by anti-TF 5G9. Spreading on anti-TF is ␤1 integrin-dependent, indicating functional interactions of the TF extracellular domain 5G9 epitope (a presumed integrin-binding site) and integrins. Recombinant TF extracellular domain supports adhesion of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
180
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(185 citation statements)
references
References 59 publications
(99 reference statements)
5
180
0
Order By: Relevance
“…5 Concomitantly, fresh leukemia samples also expressed the VEGF receptor KDR, thus indicating, as above suggested, the possibility of an autocrine pathway in which the tumor cells may stimulate their own growth after VEGF exposure. 37,38 In addition, almost all the blast samples showing increased TF and VEGF levels also exhibited enhanced ERK phosphorylation in agreement with previous studies, which demonstrated that some transcription factors regulating TF can also induce VEGF transcription. 5 Accordingly, MAPK seems to be a common pathway that regulates, independently, VEGF and TF expression and, at the same time, is involved in the control of TF or VEGF expression induced by each other.…”
Section: Angiogenesis In Hematologic Malignanciessupporting
confidence: 90%
See 2 more Smart Citations
“…5 Concomitantly, fresh leukemia samples also expressed the VEGF receptor KDR, thus indicating, as above suggested, the possibility of an autocrine pathway in which the tumor cells may stimulate their own growth after VEGF exposure. 37,38 In addition, almost all the blast samples showing increased TF and VEGF levels also exhibited enhanced ERK phosphorylation in agreement with previous studies, which demonstrated that some transcription factors regulating TF can also induce VEGF transcription. 5 Accordingly, MAPK seems to be a common pathway that regulates, independently, VEGF and TF expression and, at the same time, is involved in the control of TF or VEGF expression induced by each other.…”
Section: Angiogenesis In Hematologic Malignanciessupporting
confidence: 90%
“…Thus, TF-VIIa signaling may simultaneously counteract integrin suppression by phosphorylating the TF cytoplasmic domain and locally triggering proinvasive PAR2 activation. 37 Finally, thrombin generation downstream of TF also plays a central role in the metastatic process, and thrombin's effects on tumor cells are generally assumed to be mediated by PAR1. Expression of PAR1 in tumor cells has been associated with increased tumor invasiveness and metastasis.…”
Section: Tumor Progression: Tf As An Effector Of Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TF affects tumor angiogenesis in colorectal cancer and breast cancer models, through TF:VIIadependent protease-activated receptor-2 (PAR-2) activation (9)(10)(11), resulting in expression of VEGF, IL-8, MMP-7, and CXCL-1 (10)(11)(12)(13). In addition, TF binds ␣3␤1 and ␣6␤1 integrins, and disruption of this complex downregulates pro-angiogenic signaling and suppresses tumor growth in vivo (11,14).…”
mentioning
confidence: 99%
“…Is PDI able to bridge the interaction between TF and PAR2, or is there a direct TF:PAR2 interaction? Ruf and colleagues (14,15) have suggested another regulatory switch whereby TF cytoplasmic tail phosphorylation promotes PAR2 signaling and simultaneously releases TF from a complex with integrins. How does PDI and TF disulfide switching fit with this model?…”
mentioning
confidence: 99%